The Presence of PDL-1 on CD8+ Lymphocytes Is Linked to Survival in Neonatal Sepsis - Lyudmila L. Akhmaltdinova; Zhibek A. Zhumadilova; Svetlana I. Kolesnichenko; Alyona V. Lavrinenko; Irina A. Kadyrova; Olga V. Avdienko; Lyudmila G. Panibratec; Elena V. Vinogradskaya (MDPI AG, 2022)
Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection. Neonatal sepsis is the main cause of death in newborns, especially preterm infants. The pathogenesis of sepsis is based on a hyper-inflammatory syndrome combined with an immunosuppressive mechanism in sepsis. This study aimed to find critical parameters that are associated with the outcome of newborns with suspected sepsis. Understanding the association might have clinical relevance for immuno-monitoring, outcome prediction, and targeted therapy. Methods: A total of 210 newborn infants no older than 4 days with suspected sepsis at admission in Karaganda (Kazakhstan) were prospectively enrolled. Blood cultures were incubated, and pathogens in positive cultures were determined by MALDI-TOF. An immunological assay for blood cell components was conducted by flow cytometry with antibody cocktails. The diagnostic criteria for neonatal sepsis were identified by qualified neonatologists and included both clinical sepsis and/or positive blood culture. The analyzed infants were grouped into non-septic infants, surviving septic infants, and deceased septic infants. The results showed that deceased septic newborns had a lower level of CD8+ lymphocytes and higher PDL-1 expression in comparison with surviving septic newborns. PDL-1 expression on CD8+ T cells might play an immunosuppressive role during neonatal sepsis and might be used as a laboratory biomarker in the future.